PENGABDIAN MASYARAKAT MELALUI IMPLEMENTASI SISTEM PAKAN OTOMATIS PADA TAMBAK IKAN BANDENG DI DESA SEBATUAN - Danial, Danial; Rajaguguk , Managam; Kurnianto, Rudi; Arsyad, M. Iqbal; Imansyah, Fitri (Universitas Mataram, 2025)
Milkfish farming is one of the main economic activities of coastal communities, including in Sebatuan Village. However, traditional farming practices still face various challenges, particularly in the aspect of feed management, which remains inefficient and tends to be wasteful. This condition not only hampers optimal fish growth but also increases the risk of environmental pollution in the ponds. To address these issues, this community service activity was carried out to implemen an automatic feeding system as an appropriate technological solution. Through a participatory approach, the implementation team and the local community collaborated in the design, training, installation, and trial phases of the system at the pond site. The results of the activity showed improvements in feed efficiency, a reduction in feed waste, and easier pond management. In addition, this initiative contributed to enhancing the farmers’ capacity to adopt simple innovations to support the sustainability of milkfish aquaculture.